2012
DOI: 10.1093/molbev/mss169
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary History of Continental Southeast Asians: “Early Train” Hypothesis Based on Genetic Analysis of Mitochondrial and Autosomal DNA Data

Abstract: The population history of the indigenous populations in island Southeast Asia is generally accepted to have been shaped by two major migrations: the ancient "Out of Africa" migration ∼50,000 years before present (YBP) and the relatively recent "Out of Taiwan" expansion of Austronesian agriculturalists approximately 5,000 YBP. The Negritos are believed to have originated from the ancient migration, whereas the majority of island Southeast Asians are associated with the Austronesian expansion. We determined 86 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
118
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(136 citation statements)
references
References 59 publications
14
118
0
2
Order By: Relevance
“…Identical patterns were observed in four communities from peninsular and island Malaysia (n = 86; Jinam et al 2012). In both cases, whole mitochondrial DNA genome sequences were generated, but only for a very small number of samples.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Identical patterns were observed in four communities from peninsular and island Malaysia (n = 86; Jinam et al 2012). In both cases, whole mitochondrial DNA genome sequences were generated, but only for a very small number of samples.…”
Section: Discussionmentioning
confidence: 78%
“…The region's prehistory is dominated by population movements, beginning with its first settlement by modern humans approximately 50 kya and continuing to the Islamization of Indonesia during the historic period. Reflecting the rich cultural and linguistic diversity of Indonesia's inhabitants, these eras have also left their mark on the genetic diversity of the individuals who inhabit Indonesia today (Cox et al 2012;Jinam et al 2012;Karafet et al 2010;Kayser 2010;Kayser et al 2003;Lansing et al 2008Lansing et al , 2009Mona et al 2009;Wilder et al 2011;Xu et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are thought to be descendants of the earliest migrants to the Southeast Asian region, along with Papuans and Australian Aboriginals (Macaulay et al 2005;Hill et al 2006). A recent analysis of mitochondrial DNA (mtDNA) complete sequences and the genome-wide autosomal single-nucleotide polymorphism (SNP) data showed that the Malaysian negritos, Philippine negritos, and Papuans appeared quite genetically distinct (Jinam et al 2012), which suggests that these may have experienced differing demographic histories and possibly reflects early divergence and long-term isolation.…”
mentioning
confidence: 99%
“…Past genetic studies regarding Malaysian negritos have focused on mtDNA (Macaulay et al 2005;Hill et al 2006Hill et al , 2007 or a specific autosomal region (Jinam et al 2010). Genome-wide SNP data have been generated in various human populations, including some Malaysian negrito populations (HUGO Pan-Asian SNP Consortium 2009; Reich et al 2011), and the availability of such data has allowed for a more targeted analysis (Yang et al 2011;Jinam et al 2012;Xu et al 2012).…”
mentioning
confidence: 99%